1994
DOI: 10.3109/07853899409148354
|View full text |Cite
|
Sign up to set email alerts
|

Compression Sonography in the Diagnosis of Deep Venous Thrombosis of the Leg

Abstract: The value of compression sonography was assessed to reduce the number of phlebographies otherwise necessary when deep venous thrombosis (DVT) is suspected among hospital patients. Compression sonography was used to study 119 prospective hospital patients who were suspected of having DVT of the lower extremity. The results were compared to those by phlebography. There were 44 DVTs detected by phlebography; ten of these were located only in the calf, below the knee. Of the remaining 34 femoropopliteal DVTs 33 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Compression sonography has been used in diagnosing symptomatic thrombosis. This technique is highly sensitive and specific for proximal DVT [14]. Furthermore, technical advances in the development of high resolution equipment, addition of color Doppler and improved individual experience of ultrasonography have lead to greater accuracy in the diagnosis of symptomatic distal DVT [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Compression sonography has been used in diagnosing symptomatic thrombosis. This technique is highly sensitive and specific for proximal DVT [14]. Furthermore, technical advances in the development of high resolution equipment, addition of color Doppler and improved individual experience of ultrasonography have lead to greater accuracy in the diagnosis of symptomatic distal DVT [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Only five other studies have reported on the use of ultrasound for the diagnosis of deep-vein thrombosis specifically in hospitalized patients (2-6). Four studies assessed the accuracy of ultrasonography by per- Table 2 Baseline characteristics of study patients with and without venous thromboembolism Table 3 Prevalence of venous thromboembolism (VTE), initially and on follow-up, according to pretest probability derived by the clinical model * includes DVT day 8 ** includes PE day 20 forming venography in all patients (2,3,5,6). The accuracy was similar to that reported in outpatients with the sensitivity for proximal deep vein thrombosis ranging from 89% to 97% and specificity 86% to 97%.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is relatively insensitive to deepvein thrombosis isolated to the calf (1) but a serial testing strategy, based on the premise that clinically significant calf vein thrombi will extend by one week and may then be detected, has proven safe in outpatients. Although dozens of studies have evaluated the accuracy and the utility of ultrasound for outpatients with suspected deep vein thrombosis, only five studies have focussed exclusively on inpatients (2)(3)(4)(5)(6). These studies suggested that ultrasound may be less accurate and less safe as a diagnostic test in hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we included 9 studies and 5126 patients to inform the effect of performing a test on patient important outcomes for patients suspected of having DVT. The references for the included studies are as follows: proximal compression ultrasound [84][85][86][87][88][89][90][91][92][93][94][95][96] ; wholeleg ultrasound [97][98][99][100][101][102][103] ; serial ultrasound 84,88,[104][105][106][107] ; D-dimer. [106][107][108][109][110][111][112][113][114][115][116][117][118][119] Low PTP/prevalence (£10%)…”
Section: Summary Of Evidencementioning
confidence: 99%